Implementation of E-Learning Among UNM Students Using the UTAUT Model - Aslinda, Ummu; Anisa M, Nurul; Irwansyah Suwahyu; Putri Maharani, Geby; Nurrahmah Agusnaya (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2025)
-learning has emerged as a crucial strategy to provide broad and easy access to high-quality education. In Indonesia, the concept of e-learning is commonly implemented in higher education institutions, including Universitas Negeri Makassar, to support student learning activities. This study aims to analyze the factors influencing students’ satisfaction with the use of e-learning by adopting the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The UTAUT model is adopted in this study because it provides measurement tools that are useful for policymakers to assess the potential success of new technology adoption. A quantitative research approach using a survey method was employed to identify the factors affecting user satisfaction and behavioral intention to use e-learning. The results indicate that students’ perceptions at Universitas Negeri Makassar toward e-learning usage align with the UTAUT model, which is reflected in their experiences using the e-learning system